Situation Report: Hungary, 3 February 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Shultz Pleased to Have Met "Wise Man" of Hungary / by Steven Koppany Hungarian Regime Sees Pravda Article as Positive / by Alfred Reisch Another Round of Price Increase / by Alfred Reisch The First Private Hotel: Hello and Goodbye / by Eva Lengyel New Gas Pact with the Soviet Union a Mixed Blessing / by Steven Koppany PPF Congress Issues Strong Plea for Continuing Reform / by Edith Markos Poet Dismisses after Controversial Literary Meeting / by Edith Markos Children's Village Struggling to Overcome Delays / by Eva Lengyel